2017 12th International Conference on Intelligent Systems and Knowledge Engineering (ISKE) 2017
DOI: 10.1109/iske.2017.8258734
|View full text |Cite
|
Sign up to set email alerts
|

Concept drift region identification via competence-based discrepancy distribution estimation

Abstract: Abstract-Real-world data analytics often involves cumulative data. While such data contains valuable information, the pattern or concept underlying these data may change over time and is known as concept drift. When learning under concept drift, it is essential to know when, how and where the context has evolved. Most existing drift detection methods focus only on triggering a signal when drift is detected, and little research has endeavored to explain how and where the data changes. To address this issue, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Dong et al in [18] proved and showed that a well-trained defect-prediction model may output inaccurate results if the data distribution changes over time. They also proved that training a prediction model becomes more difficult in such scenarios.…”
Section: Concept-drift Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…Dong et al in [18] proved and showed that a well-trained defect-prediction model may output inaccurate results if the data distribution changes over time. They also proved that training a prediction model becomes more difficult in such scenarios.…”
Section: Concept-drift Handlingmentioning
confidence: 99%
“…The stable learner predicts (line 14), whereas the reactive one performs prediction (line 15) using the data samples in the currently processing window. The number of places in the current window where predictions of the reactive learner are correct whereas that of the stable learner are incorrect are computed (lines [16][17][18][19][20]. This count is then compared with the user-supplied threshold value for detecting drift.…”
Section: Proposed Approach Based On Plmentioning
confidence: 99%
“…This refers to the phenomenon where the statistical properties of a data stream change over time [9]. If CD is not detected, the model may become less accurate over time, leading to false positives or false negatives [10]. Therefore, there is a need for concept drift detection (CDD) methods that can identify when CD is occurring and adjust the model accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…CD can have a significant impact on the accuracy of JIT-SDP models. If CD is not detected and accounted for, the model may become less accurate over time, leading to false positives or false negatives (Dong, Lu et al 2017). By detecting and addressing concept drift in JIT-SDP models, organizations can improve their ability to identify and address software defects before they become critical issues.…”
Section: Introductionmentioning
confidence: 99%